Peningkatan Pengetahuan Remaja Putri Tentang Risiko Obstetri Akibat Pernikahan Dini - Surtikanti Surtikanti; Ayu Sunarti. S; Rosdiana Rosdiana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Early marriage remains a major reproductive health issue in Indonesia, leading to various obstetric risks such as pregnancy complications, premature delivery, and increased maternal mortality among young women. This community service activity aimed to improve adolescent girls’ knowledge about obstetric risks due to early marriage through participatory health education. The program was conducted at junior and senior high schools under the working area of Puskesmas X, Kota Y, in August 2025, involving 40 adolescent girls aged 13–17 years. The implementation methods included interactive lectures, group discussions, educational video screenings, and distribution of information leaflets. Evaluation was performed using pre-test and post-test questionnaires. The results showed an increase in average knowledge scores from 56.3 (moderate) to 87.4 (good), with an improvement rate of 55%. Participants demonstrated high enthusiasm and were able to identify at least three obstetric risks associated with early marriage, such as anemia, bleeding, and preterm delivery. The activity successfully raised awareness among adolescent girls about the importance of delaying marriage until an ideal age and strengthened collaboration between academics, health workers, and schools in preventing early marriage.